Gene Expression Profile of T-cell Receptors in the Synovium, Peripheral Blood, and Thymus during the Initial Phase of Collagen-induced Arthritis - Kim, Ji-Young; Lim, Mi-Kyoung; Sheen, Dong-Hyuk; Kim, Chan; Lee, So-Young; Park, Hyo; Lee, Min-Ji; Lee, Sang-Kwang; Yang, Yun-Sik; Shim, Seung-Cheol (Immune network, 2011)
Current management strategies attempt to diagnose rheumatoid arthritis (RA) at an early stage. Transcription profiling is applied in the search for biomarkers for detecting early-stage disease. Even though gene profiling has been reported using several animal models of RA, most studies were performed after the development of active arthritis, and conducted only on the peripheral blood and joint. Therefore, we investigated gene expression during the initial phase of collagen-induced arthritis (CIA) before the arthritic features developed in the thymus in addition to the peripheral blood and synovium. For gene expression analysis using cDNA microarray technology, samples of thymus, blood, and synovium were collected from CIA, rats immunized only with type II collagen (Cll), rats immunized only with adjuvant, and unimmunized rats on days 4 and 9 after the first immunization. Arrays were scanned with an Illumina bead array. Of the 21,910 genes in the array, 1,243 genes were differentially expressed at least 2-fold change in various organs of CIA compared to controls. Among the 1,243 genes, 8 encode T-cell receptors (TCRs), including CD3ζ, CD3δ, CD3ε, CD8α, and CD8β genes, which were down-regulated in CIA. The synovium was the organ in which the genes were differentially expressed between CIA and control group, and no difference were found in the thymus and blood. Further, we determined that the differential expression was affected by adjuvant more than Cll. The differential expression of genes as revealed by real-time RT-PCR, was in agreement with the microarray data. This study provides evidence that the genes encoding TCRs including CD3ζ, CD3δ, CD3ε, CD8α, and CD8β genes were down-regulated during the initial phase of CIA in the synovium of CIA. In addition, adjuvant played a greater role in the down-regulation of the CD3 complex compared to CII. Therefore, the down-regulation of TCR gene expression occurred dominantly by adjuvant could be involved in the pathogenesis of the early stage at CIA.